ON DATA DIMENSIONALITY REDUCTION AS APPLIED TO SOLVING CLASSIFICATIVE GEOLOGICAL-GEOPHYSICAL PROBLEMS - KURHANSKYI, V.; TISHAIEV, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
In article briefly review the questions of data dimensionality reduction as applied to solving classification geological-geophysical problems. Linear and nonlinear principal-factor methods work showing on the model expamples.